The Vernacular World of Pu Songling : Popular Literature and Manuscript Culture in Late Imperial China - Lu, Zhenzhen, (Asian Studies E-Books Online, Collection 2026., 2025)
This study presents a lively world of vernacular writing from Zichuan, Shandong, the home region of Pu Songling (1640-1715). Based on Keio University's Liaozhai Collection, it examines a world of local reading and writing through the manuscripts of village scholars, including those of a topolectal primer and various song-narratives attributed to the author famed for his classical tales Liaozhai zhiyi . The study sheds light on intertwined realms of local textual transmission, the place of manuscript culture in ordinary literary life, and the role of language and locality in shaping the plural literatures of late imperial China.